Analysis of Peter Senge's Five Commandments Learning in Organizations and Adherence to the Islamic Azad University Staff of its Components - Rasol Fanikhayavi; Nooshin Mardani; Sheida Mardani (CES Working Papers, 2014)
To learn problem solving and the development of learning organizations has been added to the agenda; Therefore, organizational learning and ultimately, learning organizations, that meet the needs of current challenges such as environmental change, competition and quality are met. Peter Senge's five commands or discipline research and case study data, the compliance staff of Ardebil University defines these components. A descriptive study - a survey of the Islamic Azad University of Ardabil province were done in 2010. All statistics are community college employees that using stratified sampling 205 employees were selected as examples. Data collected by questionnaire in two parts with the scientific validity and reliability were 82%. By using SPSS research data were analyzed. The average amount of free functionality of the personal staff of employees with 10/18, The mental models with 92/17, the common cause against 87/16, after learning 94/16 and an average rate of systemic thinking employees with 14/17. Due to low compliance with the recommended five dimensions of learning organization mechanisms for universities to be respected by the authorities; to the staff of the University and the observed rate of learning will lead to the optimal level.
Keywords: I2; G00; 330; Learning organizations; Peter Senge's five commands; Staff; Islamic Azad University Romania